The effects of seasonal, sex and size on the digestive enzyme activities in freshwater crayfish (Astacus leptodactylus Eschscholtz, 1823). (3rd February 2018) - Bahadir Koca, Seval; Acar, Esra; Naz, Mehmet
Abstract: The effects of seasonal, sex and size on digestive enzyme activities of Astacus leptodactylus in natural habitat were investigated in the present study. The freshwater crayfish were sampled 584 individual as seasonally from Egirdir Lake. Ten male and 10 female individuals were sampled randomly from caught crayfish in each two different size ranges (4.5–7.0, 7.1–9.9 cm) and each season. The gastrointestinal tract, gastric, intestine and midgut gland were individually dissected on ice for enzyme analysis and stomach contents. At the end of the study, amylase activities were affected by interaction of season × sex × size in intestinal, season × sex in midgut gland. However, any interaction was not determined in amylase activities of the gastric. Lipase activities were affected by interaction of season × sex × size in intestinal and gastric, season × sex in midgut gland. The protease activities in each organ were affected by interaction of season, sex and size ( p ˂ .05). In all organs, amylase and lipase activities were similar. However, the highest protease activity was in stomach while the lowest protease activity was the intestine. The protease activities were higher than amylase and lipase activities. There is a positive correlation between protease enzyme activities in gastric with gonad maturation and active feeding period. It can be said based on data of digestive system and high protease activity that A. leptodactylus is an omnivore species in need high protein. In addition, the reason for the low levels of lipase activity may be A. leptodactylus not prefer high fat foods or not fed high fat foods.